Interaction between plant phenolics and rice protein improved oxidative stabilities of emulsion. (September 2019) - Jia, Xiao; Zhao, Mouming; Xia, Ning; Teng, Jianwen; Jia, Chunxiao; Wei, Baoyao; Huang, Li; Chen, Dewei
Abstract: The interaction between rice protein isolate (RPI) and ferulic acid (FA) was systematically investigated. The results showed that fluorescence intensity of the RPI decreased gradually upon increasing the concentration of ferulic acid, and the maximum emission shifted from 352.0 to 359.2 nm. It was proposed that a static quenching of RPI-FA complex occurred, due to the hydrophobic interactions. Moreover, CD spectra and FT-IR spectroscopy data suggested that the concentration of β-turn and α-helix decreased while those of random coil and β-sheet increased in RPI-FA complex. The decrease of intensity of the amide I band and amide II band in the RPI-FA complex implied a significant reduction of protein α-helical structure and the presence of non-polar hydrophobic interactions. In addition, SDS-PAGE results demonstrated that ferulic acid reacted with glutelin acidic subunits (34–37 KDa) as well as globulin (26 KDa), and ferulic acid might bind with aromatic amino acid residues of RPI. Furthermore, the RPI-FA complex exhibited high DPPH scavenging ability, ABTS + scavenging ability and ORAC value. Finally, emulsion stabilized by RPI-FA complex could decrease the concentration of hydroperoxide, TBARS, and hexanal, thereby effectively restraining fat oxidation degradation. Graphical abstract: Image 1 Highlights: Rice protein isolate and ferulic acid were interacted by hydrophobic interactions. Ferulic acid reacted with gluten acid subunits and globulin of RPI. RPI-FA complex could improve the oxidative stability of corn oil in emulsion.